Microfluidic-based linear-optics label-free imager. Issue 7 (4th March 2020) - Wagner, Omer; Edri, Eitan; Hadikahani, Pooria; Shpaisman, Hagay; Zalevsky, Zeev; Psaltis, Demetri
Abstract : Microfluidic channel flows and traps biological samples inside a water droplet along with suspended nanoparticles. Linear optics nanoscopy is then used to image the sample by decoding the scattered light from the nanoparticles in its vicinity. Abstract : Linear optics based nanoscopy previously reached resolution beyond the diffraction limit, illuminating samples in the visible light regime while allowing light to interact with freely moving metallic nanoparticles. However, the hydrodynamics governing the nanoparticle motion used to scan the sample is very complex and has low probability of achieving appropriate and fast mapping in practice. Hence, an implementation of the technique on real biological samples has not been demonstrated so far. Moreover, a suitable way to perform controlled nanoparticle scanning of biological samples is required. Here we show a solution where a microfluidic channel is used to flow and trap biological samples inside a water droplet along with suspended nanoparticles surrounded by silicone oil. The evanescent light scattered from the sample and is rescattered by the nanoparticles in the vicinity. This encodes the sub-wavelength features of the sample which can later on be decoded and reconstructed from measurements in the far field. The microfluidic system-controlled flow allows better nanoparticle scanning of the sample and maintains an isolated system for each sample in each droplet. A more localized scan at the droplet water/oil interface is also conducted using amphiphilic nanoparticles where their hydrophilic side is constrained to the droplet and their hydrophobic side is constrained to the oil. This allows higher probability of capturing evanescent fields closer to their origin, yielding better resolution and a higher signal to noise ratio. Using this system, we obtained images of an E. coli sample and demonstrated how the method yield fine resolution of the sample contours. To the best of our knowledge, this is the first time that a linear and label free optics imaging process was performed using a micro-fluidic device.